Phylogeography of a neotropical montane forest ovendird (premnoplex brunnescens; furnariidae): the influence of the complex topography and dynamic history of the andes on evolutionary differentiation (2010)
The spatial and temporal aspects of Neotropical montane bird diversification are not well established. Here, we use a large sample of mitochondrial and nuclear DNA sequences to examine the effect of geographical barriers and historical events on intraspecific differentiation of Premnoplex brunnescens, a broadly distributed ovenbird occurring in montane forests in South and Central America. We found highly genetically differentiated populations on opposite sides of inter-Andean river valleys, lowland arid regions and ridge lines. Molecular dating revealed that intraspecific divergences occurred between the Late Pliocene and the Pleistocene, suggesting that the final uplift of the Andes and more recent climatic fluctuations influenced population genetic differentiation at multiple temporal levels. Reconstructions of historical demography based on coalescent models revealed historical fluctuations in population sizes, suggesting that populations tracked the expansions and contractions of montane forests associated with Pleistocene glacial cycles. Our study underscores the need for additional phylogeographic studies of Andean taxa to obtain a comprehensive understanding of the processes influencing intraspecific diversification in the Neotropical montane region.